Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content:1. Innovation and its role in industrial excellence and the development of logistics services in KSADr. Vivian Mohammed Saleh Nasrulddin, Mrs. Tharaa Hassan Omar Alidrisi2. The Moderating role of Information Technology in the relationship between the Re-Engineering of Administrative Processes and The Institutional Performance of the Yemeni General Electricity Corporation (2018-2022)Mr. Munif Ahmed Saif Al-Muhrami , Prof. Nahg AbdulMajid Alawi3. The Impact of Applying Governance Mechanisms on Corporate Social Responsibility Disclosure in Saudi BanksCo-Prof. Maha Faisal Alsayegh, Mrs. Nawal Mohammed Aljuaid4. The legal system for threatening fines in civil lawsuits according to the Saudi systemDr. Randa Mustafa Hassan Suliman5. The extent to which health insurance indicates the efficiency of healthcare centers in KSADr. Vivian Mohammed Saleh Nasrulddin, Mrs. Amal Ghazi Alnahdi, Mrs. Esraa Ahmad Bokhari6. The reality of brainstorming among students of the Academic Complex of Al-Mahalla Colleges at King Khalid University and the importance of strategic planning in its developmentAsst-Prof. Reda Abdelfattah Ibrahim Mohamed, Co-Prof. Ehsan Ibrahim Allah Gabu Ibrahim7. The touristic values of Jordan pavilion at Expo 2020 Dubai and its most prominent challenges from visitors’ standpointMrs. Suad Fayez Malkawi8. Analysis of the performance of Khartoum Customs Department during the period 2019-2021Dr. Akram Abd Eldaim Mohammed
Keywords: Journal of Economic, Administrative and Legal Sciences